If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 123 + -5x = 40x + 23 Reorder the terms: 123 + -5x = 23 + 40x Solving 123 + -5x = 23 + 40x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-40x' to each side of the equation. 123 + -5x + -40x = 23 + 40x + -40x Combine like terms: -5x + -40x = -45x 123 + -45x = 23 + 40x + -40x Combine like terms: 40x + -40x = 0 123 + -45x = 23 + 0 123 + -45x = 23 Add '-123' to each side of the equation. 123 + -123 + -45x = 23 + -123 Combine like terms: 123 + -123 = 0 0 + -45x = 23 + -123 -45x = 23 + -123 Combine like terms: 23 + -123 = -100 -45x = -100 Divide each side by '-45'. x = 2.222222222 Simplifying x = 2.222222222
| 23/7= | | x^2-0.05x+0.0006=0 | | 6y-3=4y+2 | | =5h+2p | | ((0.03-x)*(0.02-x))=0 | | (2x-3)(x-5)=(x-6)(x-3)-3(X-1) | | 6n+8=2n+36 | | 3a-5b-8a+b= | | 5n+4=2n+22 | | (2x-3)=(x-5) | | 29+.08m=46.12 | | 3x+5=x-16 | | .33333333z+.16666667=5.16 | | 12p-3q-10p+9q-2p-6q= | | 3x+2x=91.50 | | 8p+4q-4p-2q-3q+9p= | | 0=x^2-7x+12 | | 12g+3g-9g-g= | | x^2-8x+14-7+5a-3a-2a=112 | | 5x+2(-3x-2)=1-6x | | -(7y-1)-(-6y+6)=7 | | 7a-3(a-1)=51 | | 0=6x^2-23x+20 | | 7/8-5/8=2 | | 2x+4(x-6)=12 | | 9x+3x=20 | | 62=7x+6 | | 138=11x+17 | | 16(x-7)=-4(x+38) | | 6(x+8)=5x+54 | | 6x^2+58x+105=0 | | 14=2/3(9y-15) |